Prevalence of Cataract and Its Associated Risk Factors Among Ophthalmology Clinics Visitors Age More Than 40 Years Old Sana'a, Yemen, 2025 Hospital Based Study - Al-Gharasi, Siham Mohsen Hussein; Al-Gharasi, Aisha Mohammed Ameen; Hamzah, Nada Salah Aldeen Abdo; Sanhoop, Shaima Khaled Mohammed (My University, 2025)
Background: A cataract is the opacification of the eye's natural crystalline lens, which diminishes transparency and impairs light transmission, resulting in progressive vision loss or blindness. Aim: To assess the prevalence of cataract and identify its associated risk factors among visitors to ophthalmology clinics in Sana'a, Yemen, in 2025.